A comparison effect of aircraft main gear configuration on runway damages by LED and FE method. Issue 2 (3rd May 2016) - Shafabakhsh, Gholam Ali; Kashi, Ehsan; Akbari, Abbas
Abstract : Purpose: This paper aims to apply a pavement design by LEDFAA for a sample airport, and design results involving layer thickness, modulus and cumulative damage factor (CDF) achieved are shown in figures. Design/methodology/approach: Finite element (FE) simulation is applied for sample airport pavement and based on results involving stress and strain, CDF amount is shown by using related equations. To analyze the accuracy of modeling, a comparison has been made between the values of ABAQUS and case study results at Denver International Airport (DIA). Findings: The present study includes a comparison between the two conventional methods for runway pavement design. There is linear relation between layered elastic design (LED) and FE method results, so CDF rate achieved by the FE method is always smaller than the LED method. To assess the accuracy of the applied modeling with ABAQUS software, the validation was done using the deformations under the concrete slabs of DIA. The results are compatible with the results acquired from the case study, and the high accuracy of modeling was approved. This research shows that B-777 on rigid pavements and A-340-500/600 on flexible pavements have the most CDF contribution, among other aircrafts. Also, CDF rate for any aircraft in the LED method is higher than the FE method. Originality/value: To assess the accuracy of the applied modeling with ABAQUS software, the validation was done using the deformations under the concrete slabs of DIA. The results are compatible with the results acquired from the case study, and the high accuracy of modeling was approved.